Investigation of mislabeling and unpermitted additives in commercially available Indian weaning foods: A case study - Aravapally Rishika; Sravanika Bezawada Sree Sesha; Shaw Amrita; Gupta Jhinuk (BIO Web of Conferences)
The Food suitable for babies during the weaning period is known as weaning foods. It plays a crucial role in nutrition, growth and development of children. The availability of ready-to-eat, commercial baby foods help working parents by providing quick and reliable feeding options However, discrete incidences reported on mislabeling in such products are matter of concern. Mislabeling in weaning foods may lead to serious risks, such as obesity from over consumption of carbohydrate and fat or cognitive issues caused by harmful additives. Current popularity and ever-increasing demand for such products make weaning food market highly vulnerable towards mislabeling and adulteration. Therefore, it is important to assess the occurrence and severity of mislabeling in weaning foods, test the accuracy of their nutritional labels and check the presence of harmful preservatives and colorants. In this project, a total of 110 such products, available on online platforms, were manually screened to detect any forms of labeling violations. Ten products, which showed maximum occurrence of labeling violations, were selected for quantitative estimation of fat, carbohydrate and detection of unpermitted colors and preservatives such as Metanil yellow, Malachite green, Butylated Hydroxy Anisole (BHA) and Butylated Hydroxy Toluene (BHT). 70% of the 110 screened products showed mislabeling in one or multiple forms. Printed and estimated values of carbohydrate and fat did not match in majority of the tested samples. Content variation was detected as high as 114% (for carbohydrate) and 400% (for fat). BHA was present in 40% samples, revealing the lack of chemical food safety in the ready-to-eat weaning foods.